2008
DOI: 10.1007/s11605-007-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of the Metastatic Lymph-Node Ratio in Early Gastric Cancer

Abstract: The metastatic lymph-node ratio has important prognostic value in gastric cancer; this study focused on its significance in early gastric cancer. In total, 1,472 patients with early gastric cancer underwent curative gastrectomy between 1992 and 2001. Of these, 166 (11.3%) had histologically proven lymph-node metastasis. Prognostic factors were identified by univariate and multivariate analyses. Metastasis was evaluated using the Japanese Classification of Gastric Carcinoma (JGC) and the Union Internationale Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 18 publications
2
32
1
Order By: Relevance
“…The results of univariable and multivariable analyses of potential prognostic factors in this study showed that the rN category was one of the independent prognostic parameters. Kunisaki et al [21] analyzed 1472 early gastric cancer patients undergone curative gastrectomy, and found that rN can identify subsets of patients with a significantly different survival rate within UICC/TNM pN1, pN2 and pN3 categories, suggesting that the outcome of patients with the same number of metastatic nodes, or with a larger number of retrieved LNs, is unfavorable. In the present study, however, a significant difference was observed in survival rates between lymphnode stages classified by the rN category or by the UICC pN category, but no significant difference was found in survival rates between lymph-node stages classified by the UICC pN category or by the rN category, indicating that the UICC/TNM classification can demonstrate stage migration and heterogeneous stratification for disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…The results of univariable and multivariable analyses of potential prognostic factors in this study showed that the rN category was one of the independent prognostic parameters. Kunisaki et al [21] analyzed 1472 early gastric cancer patients undergone curative gastrectomy, and found that rN can identify subsets of patients with a significantly different survival rate within UICC/TNM pN1, pN2 and pN3 categories, suggesting that the outcome of patients with the same number of metastatic nodes, or with a larger number of retrieved LNs, is unfavorable. In the present study, however, a significant difference was observed in survival rates between lymphnode stages classified by the rN category or by the UICC pN category, but no significant difference was found in survival rates between lymph-node stages classified by the UICC pN category or by the rN category, indicating that the UICC/TNM classification can demonstrate stage migration and heterogeneous stratification for disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…This parameter reflects both tumor characteristics (number of metastatic lymph nodes) and therapeutic measure (extend of lymph node dissection) and has proved to be a good alternative to prevent the stage migration phenomena. In addition, it is applicable in cases when fewer than 15 lymph nodes were dissected or when D 1 lymphadenectomy or noncurative resection was performed [6][7][8][9][10][11][12][13]26].…”
Section: Discussionmentioning
confidence: 99%
“…To resolve these limitations, recently n ratio as a new prognostic factor has been proposed by several authors [14,15,18,26].Ithasprovedtobeagoodalternativetoprevent thestagemigrationphenomenon,anditisalsousableinpatientswith<15lymphnodesdissected,orD1lymphadenec-tomy,ornoncurativeresection [14][15][16][17][18][19][20][21] 04;table2,fig.2). …”
Section: Discussionmentioning
confidence: 99%
“…Gastriccancerisstilloneofthemostfrequenttumorsandthe leadingcauseofcancerdeathintheworld.Althoughtheincidenceratehasdeclined,itsprognosishasnotimprovedmuch, andthecumulative5-yearssurvivalratesofallpatientswith gastriccancerhavechangedonlyslightlyoverthepast4dec-adesbutremainunder20% [1,2].Surgeryrepresentsthecornerstone of any curative procedure. A correct definition of poorprognosticfactorsmayhelptoguidemoreaggressiveadjuvanttreatmentsprotocolspostoperatively [3,4].…”
Section: Introductionmentioning
confidence: 99%